2020
DOI: 10.1002/bit.27471
|View full text |Cite
|
Sign up to set email alerts
|

On the donor substrate dependence of group‐transfer reactions by hydrolytic enzymes: Insight from kinetic analysis of sucrose phosphorylase‐catalyzed transglycosylation

Abstract: Chemical group‐transfer reactions by hydrolytic enzymes have considerable importance in biocatalytic synthesis and are exploited broadly in commercial‐scale chemical production. Mechanistically, these reactions have in common the involvement of a covalent enzyme intermediate which is formed upon enzyme reaction with the donor substrate and is subsequently intercepted by a suitable acceptor. Here, we studied the glycosylation of glycerol from sucrose by sucrose phosphorylase (SucP) to clarify a peculiar, yet ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…Especially in the early reaction phase (~ 5 h), LmSucP produced more glucose than BaSucP. This observation was consistent with a recent kinetic study that showed BaSucP to exhibit higher reaction selectivity (glycosylation of glycerol compared with hydrolysis) than LmSucP [ 63 ]. (3) Both enzymes formed 1-GG as secondary glycosylation product to GG.…”
Section: Resultssupporting
confidence: 89%
“…Especially in the early reaction phase (~ 5 h), LmSucP produced more glucose than BaSucP. This observation was consistent with a recent kinetic study that showed BaSucP to exhibit higher reaction selectivity (glycosylation of glycerol compared with hydrolysis) than LmSucP [ 63 ]. (3) Both enzymes formed 1-GG as secondary glycosylation product to GG.…”
Section: Resultssupporting
confidence: 89%
“…The retaining trehalose phosphorylases (THP), on the other hand, are believed to follow a direct front-side nucleophilic displacement, often referred to a so-called internal return-like mechanism [ 33 ]. In this case, the glycosidic oxygen is protonated by a phosphate hydroxyl group, and the glycosidic bond is destabilized by a nucleophilic attack at C-1 atom with the oxygen atom donating a proton to the glycosidic oxygen [ 34 ]. As Fig.…”
Section: Overview Of Disaccharide Phosphorylasesmentioning
confidence: 99%
“…In this context, glycoside phosphorylases have attracted increasing attention as biocatalysts for glycosyl transfer [21] . In vivo , they catalyze the degradation of di‐ and oligosaccharides with inorganic phosphate, but the reaction is readily reversible in vitro due to the high energy content of the synthesized glycosyl phosphate [22] .…”
Section: Introductionmentioning
confidence: 99%